Study of Knowledge and Attitudes of Food Handlers in Food Processing at the Beach Pogaian Diner, Tomini Village, Tomini District of Parigi Moutong - Dela; Budiman; Eka (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Food processing is a method or technique to change raw material becomes food or another form that is readily consumed by human being, begun from preparation of food processing like making and ready food to serve. The objective of this research is to find out study of knowledge and attitude off food touchers inprocessing food pogain beach diner, tomini village, tomini district of parigi moutong. This research used qualitive method descriptive approach. Data obtained through process of in the indepenth interview to the people who are considered to know about field situation that was searched. All data that have been collected become the key toward what is searched. Research finding according to informant’s description can be concluded that cnowledge of food touchers is still low concerning with hygine, sanitation of food processing and as well as attitude of food touchers still lack of payimg attention to hygiene, sanitation of food processing. The research finding is expected to increase hygine sanitation of food processing.